Latitudinal and Habitat‐Driven Diversity of Coastal Fishes in the Southernmost Southwest Atlantic Ocean - Pablo J. Merlo; Agustín De Wysiecki; Leonardo A. Venerus; Gastón A. Trobbiani; Alejo J. Irigoyen (Journal of Biogeography, 2025)
Aim To evaluate alpha and beta diversity of coastal marine fishes across different spatial scales—habitat, regional, and biogeographical—along a 14° latitudinal gradient (41° S–55° S). Location Southern Southwest Atlantic Ocean (SWA). Taxon Coastal marine fishes. Methods We sampled four benthic habitats—rocky reefs, soft bottoms, transition habitats, and kelp forests—across seven shallow coastal sites (≤ 30 m depth) spanning distances of up to 1500 km. We conducted a total of 335 hourly deployments by using Baited Remote Underwater Video Stations (BRUVS). We analysed the alpha diversity by site and habitat and assessed beta diversity along with the influence of environmental variables across different spatial scales. Furthermore, we identified key taxa contributing to compositional changes. Results We recorded 7045 individuals representing 32 fish taxa: 30 species, one genus— Patagonotothen— and one family—Myxinidae. Taxonomic richness decreased with latitude, and a gradual turnover in species composition was recorded along the latitudinal gradient. This turnover distinguished warm‐temperate assemblages of the Argentine Biogeographic Province from cold‐water assemblages of the Magellanic Province and disclosed a southwards displacement of the biogeographic transition zone between them. In the Argentine Province, four species were identified as recent colonisers from lower latitudes. In addition, benthic habitats showed relatively high species turnover, with 25% of the recorded taxa being exclusive to a single habitat. Main Conclusions This study represents the first standardised BRUVS survey conducted across such an extensive spatial scale in the SWA, and one of the broadest latitudinal assessments using this method globally. Our findings fill a knowledge gap in high‐latitude fish biogeography, reveal climate‐driven shifts in fish assemblages in the SWA, and highlight the contribution of different benthic habitats to overall fish diversity. Our study also uncovers scale‐dependent patterns in marine coastal fish assemblages and has implications for their monitoring and management.